2005
DOI: 10.1080/01421590400019484
|View full text |Cite
|
Sign up to set email alerts
|

Role-playing for more realistic technical skills training

Abstract: Clinical skills are an important and necessary part of clinical competence. Simulation plays an important role in many fields of medical education. Although role-playing is common in communication training, there are no reports about the use of student role-plays in the training of technical clinical skills. This article describes an educational intervention with analysis of pre- and post-intervention self-selected student survey evaluations. After one term of skills training, a thorough evaluation showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 11 publications
2
52
0
5
Order By: Relevance
“…High-fidelity simulations offer a potentially effective tool for engaging critical thinking skills of pre-professional nursing students, prompting them to think more like seasoned practitioners. As noted by Comer (2005) and Nikendei et al (2005), and confirmed by the results of this study, even though the students play different roles during the simulation and their behavior patterns are very different, each student still perceives the situation as a nursing student and engages in critical thinking as afforded by the specific role played. Still, in our research setting, only a small subset of critical thinking habits of mind (reflection and contextual perspective) and skills (applying standards and logical reasoning) were observed during the simulation and follow-up debriefings, suggesting the need for additional scaffolding.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…High-fidelity simulations offer a potentially effective tool for engaging critical thinking skills of pre-professional nursing students, prompting them to think more like seasoned practitioners. As noted by Comer (2005) and Nikendei et al (2005), and confirmed by the results of this study, even though the students play different roles during the simulation and their behavior patterns are very different, each student still perceives the situation as a nursing student and engages in critical thinking as afforded by the specific role played. Still, in our research setting, only a small subset of critical thinking habits of mind (reflection and contextual perspective) and skills (applying standards and logical reasoning) were observed during the simulation and follow-up debriefings, suggesting the need for additional scaffolding.…”
Section: Resultssupporting
confidence: 84%
“…According to Bremner et al (2006), students using patient simulators improve their self confidence, decision making, and clinical performance, and become better prepared for their hospital experiences. Simulations have been shown to enhance communication skills among pre-service nurses (Nikendei et al 2005) and to increase students' motivation and self-regulation (Jeffries 2007;Mooradian 2008). Additionally, Henneman and Cunningham (2005) demonstrated that simulations helped students learn from their mistakes while enabling them to learn from others.…”
Section: Introductionmentioning
confidence: 99%
“…Role-playing may be a useful tool in communication skills training because it promotes active rather than passive learning, allows participants to experience the perspective of both physician and patient, and permits participants to practice approaches and responses in a safe environment with immediate feedback. 12 Although learner dislike of the technique has been cited as a challenge in the successful incorporation of role-playing into skill development programs, 13,14 the majority of residents participating in this program embraced role-playing as a method of practicing communication skills. A minority of residents neither enjoyed the technique nor thought that it was an effective learning tool.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional, lecture-based sessions and curricula, problem-based learning has been shown to positively affect diagnostic competencies (Schmidt et al 1996) and clerkship performance ratings in undergraduate education (Richards et al 1996;Whitfield et al 2002) as well as clinical reasoning skills in postgraduate education (Doucet et al 1998). For the acquisition of procedural skills, contextual learning is extremely important (Kneebone et al 2002;Nikendei et al 2005;Nikendei et al, 2007b). The effectiveness of skills curricula has been demonstrated using self-reports of skills performed on the ward (Remmen et al 1999), written skills tests (Remmen et al 2001) and objective structured clinical examinations in pre-post (Bradley & Bligh 1999) and comparison designs ).…”
Section: Introductionmentioning
confidence: 99%